Long-term resistance training improves speed and agility in young healthy males - Raharjo, Slamet (Universitas Suryakancana, 2024)
This study aims to prove the effect of long-term resistance training on increasing speed and agility in young healthy males. This research method was a pre-experiment with one group pretest-posttest design. A total of 15 young healthy males, aged 19-22 years participated in the study. Long-term resistance training was carried out with maximum intensity, and frequency 3x/week for 6 weeks. The data collection technique was carried out using test instruments, namely the 20-meter sprint test to measure speed and the Illinois agility test to measure agility. Measurement of speed and agility was carried out twice, namely pretest and posttest. The data analysis technique used a Paired Sample T-Test with SPSS version 25 with a significant level of 5%. Based on the results of the statistical analysis show that there was a significant difference in average agility and speed between the pretest and posttest (p ? 0.001). Based on the results of the study, it was concluded that the long- term resistance training intervention was effective in increasing the speed and agility of young healthy males.